How nonlinear control can enhance the automobile efficiency and reduce harmful emissions: China case study - Becherif, M.; Ramadan, H.S.; Cai, S. (Journal of cleaner production, 2019)
China transport energy consumption grows greatly along with dramatically escalated carbon dioxide emissions. Saving energy in transportation is requested for both reducing energy pressure intensity and decreasing relevant emissions. Large scale energy conservation and emission reduction are Chinese automotive industrys’ fundamental objectives. This paper addresses a nonlinear hybrid fuzzy based proportional integral derivative (PID) control methodology to reduce the automobile fuel over-consumption and gases over-emission. After introducing the mathematical model of the automobile Pierburg mechatronic actuator of nonlinear character with parameter uncertainties, its angular displacement is controlled via the proposed PID-fuzzy logic control (FLC) approach. The outputs of the PID controller are the entries of the series-connected FLC. The hybrid topology merges the simplicity and robustness advantages of both the classical PID and the FLC methods respectively. The feedback controller, based on FLC technique, is designed to desirably maintain the angular displacement towards their desired reference values with possible least steady state errors. The proper steady state error elimination will lead to considerable gas emission reduction together with improved energy efficiency. Through Matlab/Simulink tools, the numerical simulations significantly illustrate that the hybrid PID-FLC technique can contribute efficiently in ameliorating the system dynamic behavior in presence of parameter uncertainties. The overall system behavioral analysis enhancement and the proposed controller robustness are experimentally validated.